On f - Lacunary Statistical Convergence of Order a of Sequences of Sets - Et, Mikail; Arslanoglu, Mehmet (Amer Inst Physics, 2018)
The main purpose of this work is to introduce and examine the concepts of Wijsman f-lacunary statistical convergence of order a and Wijsman strong f-lacunary summability of order a of sequences of sets and give some relations between these concepts.
7th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 28-31, 2018 -- Kyiv, UKRAINE
Keywords: Beta; Alpha